2003
DOI: 10.1089/088922203322493067
|View full text |Cite
|
Sign up to set email alerts
|

Gp120-Alum Boosting of a Gag-Pol-Env DNA/MVA AIDS Vaccine: Poorer Control of a Pathogenic Viral Challenge

Abstract: Envelope protein immunogens may improve DNA or live-vectored HIV vaccines by complementing antiviral cellular responses with Env antibodies. We tested this concept by administering two immunizations of alum-adjuvanted HIV-1 89.6 gp120 to macaques being primed at weeks 0 and 8 with SHIV 89.6 Gag-Pol-Env DNA and boosted at week 24 with SHIV-89.6 Gag-Pol-Env recombinant modified vaccinia Ankara (MVA). Three hundred micrograms of gp120 was delivered with the second DNA prime and the MVA booster. Eight months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In another study using our Gag-Pol-Env DNA/MVA vaccine, seven additional non-A*01 macaques were protected (12). For adeno5-vectored vaccines, protection against SHIV-89.6P has been much more uniform for A*01 macaques than for non-A*01 macaques (25,29).…”
Section: Vol 79 2005 Long-term Control Of Shiv By a Low T-cell Respmentioning
confidence: 94%
“…In another study using our Gag-Pol-Env DNA/MVA vaccine, seven additional non-A*01 macaques were protected (12). For adeno5-vectored vaccines, protection against SHIV-89.6P has been much more uniform for A*01 macaques than for non-A*01 macaques (25,29).…”
Section: Vol 79 2005 Long-term Control Of Shiv By a Low T-cell Respmentioning
confidence: 94%
“…7 We also found that adding gp120 protein boosters in alum to our Gag-Pol-Env DNA/MVA protocols decreased protection. 8 Based on these findings we have undertaken the development of clade B HIV Gag-Pol-Env DNA and MVA immunogens for an HIV-1/AIDS vaccine for humans.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 gp120 was also found to inhibit major histocompatibility complex (MHC) class I presentation of Tcell epitopes of other antigen in vitro (14). More importantly, there is evidence that vaccination with gp120 can enhance viral replication and even decrease protection provided by other antigens (4,25). In a recent study the HIV envelope was reported to reduce the immune responses elicited against the HIV gag antigen by an unknown mechanism (27).…”
mentioning
confidence: 99%